Vulnerability in schizophrenia: a phenomenological anthropological approach - Irarrázaval, Leonor (Intercultural philosophy, 2018)
Abstract: Vulnerability, or simply put “the possibility of being hurt”, is not only considered a constituent aspect of human experience, illuminating essential aspects of who we are as individuals interacting with others, but it is also crucial in the manifestation of mental illness. In this paper, the specific vulnerability of patients with schizophrenia in the domain of intersubjectivity is analysed. This analysis is the result of several qualitative empirical studies and from the practice of psychotherapy. Three domains in which disturbances of intersubjectivity are manifested are described, which have been chosen because they seem relevant for psychotherapeutic purposes. Firstly, “de-personalization” is described, which implies difficulties in recognizing a sense of authorship or agency in self-experience. Secondly, “de-synchronization” is described, which refers to unilateral self-centered forms of referentiality, namely as “solipsistic” self-referentiality. In the third part, “de-contextualization” of symptomatology is described, which excludes the spatio-temporal dimension of personal history. In the conclusion, essential aspects of a “personalized” experience are revealed, emphasizing the treatment of the patient as an individual person, which might be a challenge to traditional, rather “impersonal” (and “ahistorical”) accounts of phenomenological psychopathology.